Spatial equilibrium, market integration and price exogeneity in dry fish marketing in Nigeria: A vector auto-regressive (VAR) approach - Mafimisebi, Taiwo E. (2012)
Fish is the cheapest animal protein source in Nigeria, and dry fish in particular has the potential to solve the pervasive protein shortage problem owing to its relative affordability compared with fresh fish. Boosting dry fish consumption will entail retail price reduction which is achievable only if the market for dry fish operates efficiently. This study, after testing and correcting price series for non-stationarity, modelled marketing efficiency in 66 pairs of spatially separated markets. The unit root test was used to reveal the order of econometric integration of the price series. All price series showed non-stationarity at their levels (P<0.05), but on first-differencing, they all rejected the null hypothesis of non-stationarity. This confirmed that they were generated by the same stochastic processes and, thus, capable of exhibiting long-run spatial equilibrium. The vector auto-regressive test showed that 59.1% of the markets had prices which were spatially integrated on the long-run. The Granger-causality model revealed that prices in Bauchi, Akure, Makurdi and Kano markets were driving prices in other locations. Kano market exhibited very strong exogeneity while others were either strongly or weakly exogenous. It is concluded that there is low extent of spatial pricing efficiency in Nigeria's dry fish market. The study recommended improved market infrastructures, improved information collection, collation and dissemination, and decisive policy reforms aimed at lowering retail price at the identified leader markets, as ways of enhancing spatial pricing efficiency.